Meaning construction in creative metaphors: Conventional meaning integration through «generic interfacing» in a blend, and conditions of propagation and lexicalization - Alicia Urquidi (Universitat Autònoma de Barcelona, 2015)
Given certain semantic and pragmatic conditions discussed in this article, innovative metaphors and metonymies may end in propagation and eventual lexicalization of new meanings in the language system. Paying attention to instances of creative uses of figurative language in context may provide valuable evidence for such changes in the system. Innovation creates new meaning, but creative figurative language must also recruit conventional elements into meaning construction. However, as conventional figurative and novel meaning are not processed the same way – the former tends to be processed as a comparison, the latter as more abstract categorization –, conventional elements function as generic content in novel blends. This gives rise to a phenomenon dubbed generic integration. Furthermore, cognitive processes of comprehension depend upon and give rise to pragmatic inferences that complete utterance meaning. Therefore, in order to be viable for propagation, novel metaphors and metonymies must fulfill structural iconicity, and pragmatic relevance requirements.